Preoperative Leukocytosis Imposes an Increased Risk of Recurrence and Death Among Patients With Nonendometrioid Endometrial Carcinoma. Issue 2 (1st February 2013) - Worley, Michael J.; Nitschmann, Caroline C.; Shoni, Melina; Rauh-Hain, Jose Alejandro; Williams, Kristina A.; Feltmate, Colleen M.
Abstract : Objective: To evaluate the impact of preoperative leukocytosis among patients with nonendometrioid endometrial carcinoma. Methods: The medical records of all patients with nonendometrioid endometrial carcinoma who underwent surgical treatment between January 2005 and December 2010 were retrospectively reviewed. The patients were separated into 2 groups based on the presence or absence of preoperative leukocytosis (white blood cell count ≥10, 000/μL). The groups were then compared with respect to pathologic findings, progression-free survival, and overall survival. Results: A total of 222 patients were identified, and preoperative leukocytosis was observed in 33 patients (14.9%). The leukocytosis group was associated with a larger mean size of the primary tumor (6.8 vs 4.6 cm, P = 0.016) and a greater percentage of patients with cervical stromal involvement (36.4% vs 20.1%, P = 0.039), adnexal involvement (42.4% vs. 22.8%, P = 0.017), and pelvic/para-aortic lymph node involvement (50% vs 27.4%, P = 0.025). On multivariate analysis, preoperative leukocytosis was independently associated with an increased risk of recurrence (hazard ratio, 2.07; 95% confidence interval, 1.12–3.84) and an increased risk of death (hazard ratio, 3.33; 95% confidence interval, 2.01–5.53). Conclusions: Among patients with nonendometrioid endometrial carcinoma, preoperative leukocytosis is independently associated with an increased risk of recurrence and death.